OP0167 Efficacy and safety of CNTX-4975 in subjects with moderate to severe osteoarthritis knee pain: 24-week, randomized, double-blind, placebo-controlled, dose-ranging study. (15th June 2017) - Stevens, R; Petersen, D; Ervin, J; Nezzer, J; Nieves, Y; Campbell, J; Guedes, K; Burges, R; Hanson, P
Abstract : Background: Osteoarthritis causes joint pain, stiffness, and reduced function, leading to disability. CNTX-4975, a highly purified, synthetic trans -capsaicin, targets the transient receptor potential vanilloid 1, producing analgesia via reversible deactivation of end terminals of primary afferent pain fibers within the joint and capsule. Objectives: This 24-week dose-ranging study evaluated CNTX-4975 efficacy and safety in subjects with chronic, moderate to severe osteoarthritis-associated knee pain. Methods: Subjects aged 45–80 years with chronic knee osteoarthritis, stable moderate to severe knee pain, and intolerability to oral or intra-articular analgesics were randomized to a single injection of placebo, CNTX-4975 0.5 mg, or CNTX-4975 1.0 mg. The primary efficacy endpoint was the area under the curve (AUC) for change from baseline in daily Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) A1 score through week 12. Least squares mean differences (LSMD) for CNTX-4975 vs placebo were calculated for the primary endpoint and the average weekly AUC WOMAC A1 scores using analysis of covariance. Additional efficacy endpoints, mean change from baseline in weekly WOMAC A1 score, WOMAC B stiffness subscale, and WOMAC C physical function subscale through week 24, were analyzed using a mixed model for repeated measures (MMRM). Statistical tests were 2-sided (alpha, P =0.10). Safety assessments included treatment-emergent adverse events (TEAEs). Results: Efficacy was evaluated in 172 subjects (placebo, n=69; CNTX-4975 0.5 mg, n=33; CNTX-4975 1.0 mg, n=70). Mean WOMAC A1 pain scores at baseline were 7.4 (placebo), 7.2 (CNTX-4975 0.5 mg), and 7.2 (CNTX-4975 1.0 mg). In the primary efficacy analysis, significant improvements vs placebo in WOMAC A1 scores were observed at week 12 with CNTX-4975 0.5 mg (LSMD: −0.8; P =0.07) and CTNX-4975 1.0 mg (LSMD: −1.6; P <0.0001). Significant improvements vs placebo were also observed at week 24 with CNTX-4975 1.0 mg (LSMD: −1.35; P =0.0002). In the MMRM analysis, significant improvements in WOMAC A1 scores vs placebo were demonstrated with CNTX-4975 0.5 mg at week 12 (LSMD: −0.9; P =0.087) but not week 24 (LSMD: −0.5; P =0.41), and with CNTX-4975 1.0 mg at weeks 12 (LSMD: −1.5; P =0.0003) and 24 (LSMD: −0.9; P =0.067). CNTX-4975 1.0 mg significantly improved WOMAC B (LSMD: −2.5; P =0.0013) and WOMAC C scores vs placebo (LSMD: −18.3; P =0.004) at week 12. Numerically greater improvements were observed in WOMAC B and C at week 24, but differences were not significant (WOMAC B LSMD: −1.2; P =0.14; WOMAC C LSMD: −7.2; P =0.28). In the safety population, the incidence of TEAEs was 30% for placebo or CNTX-4975 1.0 mg, and 47% for CNTX-4975 0.5 mg at week 24. Most TEAEs were considered unrelated to study treatment. Arthralgia was the most common TEAE with CNTX-4975 1.0 mg (placebo, 5.7%; CNTX-4975 1.0 mg, 7.0%). Conclusions: A single injection of CNTX-4975 1.0 mg improved pain with walking, knee stiffness, and physical function, and was well tolerated in subjects with moderate to severe osteoarthritis-associated knee pain. Disclosure of Interest: R. Stevens Shareholder of: Centrexion Therapeutics, Employee of: Centrexion Therapeutics, D. Petersen: None declared, J. Ervin: None declared, J. Nezzer Consultant for: Centrexion Therapeutics, Y. Nieves Consultant for: Centrexion Therapeutics, J. Campbell Shareholder of: Centrexion Therapeutics, Employee of: Centrexion Therapeutics, K. Guedes Shareholder of: Centrexion Therapeutics, Employee of: Centrexion Therapeutics, R. Burges Shareholder of: Centrexion Therapeutics, Employee of: Centrexion Therapeutics, P. Hanson Shareholder of: Centrexion Therapeutics, Employee of: Centrexion Therapeutics